A comparative study evaluates the effect of Hydrogen peroxide 38% and Carbamide peroxide 35% bleaching products on enamel microhardness (In vitro study) (Mustansiria Dental Journal, 2018)
The aim of this study was to compare the effect of two professional bleachingproducts (in-office Opalescence Boost hydrogen peroxide 38%) and (home bleachingOpalescence carbamide peroxide 35%) on enamel microhardness.The sample consist of thirty maxillary first premolars teeth (freshly extracted),caries free obtained from children aged 12 years old under routine orthodontictreatment. The teeth were sectioned mesiodistally parallel to the long axis of tooth andmounted on acrylic mold. The specimens were divided into two halves buccal andpalatal as per treatment, the buccal half served as experimental, while the palatal halfserved as control (1) and kept in artificial saliva at 37c0 for two weeks. Microhardnesstest were obtained before and after bleaching.Results indicated that teeth specimens submitted to Opalescence carbamideperoxide 35% showed highly significant reduction in enamel microhardness P0.05.In this study Opalescence carbamide peroxide 35% leads to the significantdecrease in enamel microhardness compared to Opalescence Boost hydrogenperoxide 38%.